Transient and permanent error control for networks-on-chip - Yu, Qiaoyan (Springer New York, 2012)
This book addresses reliability and energy efficiency of on-chip networks using a configurable error control coding (ECC) scheme for datalink-layer transient error management. The method can adjust both error detection and correction strengths at runtime by varying the number of redundant wires for parity-check bits. Methods are also presented to tackle joint transient and permanent error correction, exploiting the redundant resources already available on-chip. A parallel and flexible network simulator is also introduced, which facilitates examining the impact of various error control methods on network-on-chip performance. Includes a complete survey of error control methods for reliable networks-on-chip, evaluated for reliability, energy and performance metrics; Provides analysis of error control in various network-on-chip layers, as well as presentation of an innovative multi-layer error control coding technique; Presents state-of-the-art solutions to address simultaneously reliability, energy and performance; Describes configurable error management solutions and their hardware implementation details for variable noise conditions; Provides details of a flexible and parallel NoC simulator and corresponding simulation setup to achieve the reported results.